A cfd simulation study on the effect of oil leaking rate from damaged submarine pipeline - Abdul Khairul, Abd Hamid (2014)
This paper presents the simulation studies on the effect of oil leaking rate for oil leakage from damaged submarine pipelines. Oil spill are very serious issue that need to be taken care when construct and install the submarine pipeline. Due to the demand, transporting via pipeline with safety precaution is the best way to fulfil the demand. The objective of the present paper is to study the oil flows from damaged submarine pipelines with different oil leaking rate. CFD (computational fluid dynamic) simulations with GAMBIT and FLUENT software are carried out to investigate the process of oil spill from submarine pipeline to free surface. The whole computational domain is a rectangle with a length of 20 m and a height of 15 m. The length of computational domain is large enough, which is larger than the longest horizontal distance the oil droplets migrate when they reach the sea surface. Water occupies the lower region with height of 14.5 m, while air occupies the upper region. The damage submarine pipeline with the outside diameter (OD) of 0.6 m. The size of leakage hole (d) is a variable ranging from 0.01 m to 0.05 m with increment of 0.01 m, in order to examine the effect of leak size. GAMBIT 2.4.6 mesh-generator is employed to perform all geometry generation and meshing. From the study, the dimensionless longest horizontal distances the droplets migrate when they reach the sea surface were analysed and the fitting formulas are obtained and conduct rapid response the maximum horizontal migration distance of oil at certain time is predicted, and a forecasting model is proposed. These calculated results will provide useful guidance to place the oil containment boom. This helps to detect the leakage more accurate and precise while reduces the cost of handling